Dietary autochthonous Cetobacterium somerae CSHT supplementation enhances heat tolerance in hybrid sturgeon - Zhichao Chen; Yinshan Bai; Yuanqiong Wei; Wenhua Wu; Linmiao Li; Haoting Mai; Yepin Yu; Jinping Chen; Xiujuan Zhang (Aquaculture, 2027)

Dual effects of tidal stress on carbon turnover by biochar incorporation in estuarine wetlands: Obscuring the promotion of plant CO2 fixation while magnifying carbon stabilization of sediments - Wenxuan Mei; Haoyu Dong; Xiaoyu Gao; Haoting Liu; Lin Liu; Wei Wu; Xiaohua Fu; Lei Wang (Water Research, 2026)

Deriving health-based soil cadmium thresholds in mining-impacted agricultural regions: An integrated deterministic and probabilistic risk assessment - Haoting Tian; Shuangjiao Guo; Zhiming Liu; Xiaohui Yang; Dengfeng Wang; Aijing Yin; Pengbao Wu; Huan Zhang (Journal of Hazardous Materials, 2026)

Cyclic organic matter accumulation in a plateau salinized lacustrine basin: Major controls and hydrocarbon significance - Peng Pang; Di Xiao; Kunyu Wu; Songtao Wu; Haoting Xing; Ying Xiong; Rui Liu; Xiucheng Tan (Marine and Petroleum Geology, 2025)

Multi-shank flexible implantable neural interface for long-term olfactory neuron recording toward odor perception - Qunchen Yuan; Jiale Wang; Chunlian Qin; Shunuo Shang; Haoze Xu; Fan Wu; Yong Qiu; Haoting Zhang; Rui Sun; Ping Wang; Liujing Zhuang; Hao Wan (Chemical Engineering Journal, 2025)

Cortical microstructural alterations in different stages of Parkinson’s disease - Xueqin Bai; Tao Guo; Xiaojun Guan; Cheng Zhou; Jingjing Wu; Haoting Wu; Xiaocao Liu; Chengqing Wu; Jingwen Chen; Jiaqi Wen; Jianmei Qin; Sijia Tan; et al. (Brain Imaging and Behavior, 2024)

Association of ambient air pollution and pregnancy rate among women undergoing assisted reproduction technology in Fujian, China: A retrospective cohort study - Hua Fang; Dongdong Jiang; Ye He; Siyi Wu; Yuehong Li; Ziqi Zhang; Haoting Chen; Zixin Zheng; Yan Sun; Wenxiang Wang (Science of The Total Environment, 2024)

Cholinergic relevant functional reactivity is associated with dopamine responsiveness of tremor in Parkinson’s disease - Jingjing Wu; Cheng Zhou; Tao Guo; Xiaojun Guan; Ting Gao; Xueqin Bai; Haoting Wu; Jingwen Chen; Jiaqi Wen; Xiaocao Liu; Luyan Gu; Zhe Song; et al. (Brain Imaging and Behavior, 2022)
Tremor in Parkinson’s disease (PD) has distinct responsiveness to dopamine, which is supposed not be exclusively related to dopamine deficiency but has a close relationship with cholinergic system. This phenomenon indicates that cholinergic system may be an important regulatory for distinct dopamine responsiveness of parkinsonian tremor. Through investigating the alterations of cholinergic and dopaminergic network during levodopa administration, we aimed at exploring the mechanisms of differed dopamine responsiveness of parkinsonian tremor. Fifty-two PD patients with tremor were enrolled. MRI scanning, UPDRS III and its sub-symptom scores were collected in OFF and ON status (dopaminergic challenge test). Then, patients were divided into two groups (dopamine-resistant tremor and dopamine-responsive tremor) according to the tremor change rate median score. Dopaminergic and cholinergic network were obtained. LASSO regression was conducted to identify functional connectivity with distinct reactivity during levodopa administration between groups. Afterwards, detailed group comparisons, interaction and correlation analyses were performed. The reactivity of cholinergic connectivity showed the highest possibility to distinguish two groups, especially connectivity of right basal forebrain 123 to right parietal operculum cortex (R.BF123-R.PO). After levodopa administration, connectivity of R.BF123-R.PO was decreased for dopamine-responsive tremor while which remained unchanged for dopamine-resistant tremor. The reactivity of R.BF123-R.PO was negatively correlated with tremor change rate. Reduced cholinergic connectivity to parietal operculum may be an underlying mechanism for the responsive tremor in PD and the distinct cholinergic reactivity of parietal operculum to levodopa may be a core pathophysiology for the differed DA responsiveness of tremor in PD.

Conventional and Unconventional Hydrocarbon Resource Potential Evaluation of Source Rocks and Reservoirs: A Case Study of the Upper Xiaganchaigou Formation, Western Qaidam Basin, Northwest China - Yanchen Song; Enze Wang; Yuting Peng; Haoting Xing; Kunyu Wu; Yongxian Zheng; Jing Zhang; Na Zhang (Natural Resources Research, 2021)